2023
DOI: 10.3390/ijerph20065228
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sports Involvement on Body Image Perception and Ideals: A Systematic Review and Meta-Analysis

Abstract: Concerns about body image may affect athletes, mainly because of specific sports models to achieve successful performance. This systematic review reports on body image dissatisfaction (BID) in athletes following the guidelines for systematic reviews and meta-analyses. From a total of 887 articles identified through a systematic search of electronic databases, 15 articles conducted on 2412 athletes were included in this review. To be eligible for inclusion, the studies must have been published in the last ten y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…On the contrary, men were more satisfied with their appearance compared to women. Similar results have been reported in the study of Zaccagni and Gualdi-Russo [ 44 ]. For boys and men, the social norms are not so strict.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, men were more satisfied with their appearance compared to women. Similar results have been reported in the study of Zaccagni and Gualdi-Russo [ 44 ]. For boys and men, the social norms are not so strict.…”
Section: Discussionsupporting
confidence: 92%
“…One major challenge in assessing the effect of sport type is the varied categorizations of sport across studies and reviews. For example, classifications can be made based on aesthetic vs. nonaesthetic sports ( Zaccagni and Gualdi-Russo, 2023 ), while others consider more granular categorizations, comparing lean, feminine, and aesthetic sport athletes ( Varnes et al, 2013 ) or aesthetic, endurance, and ball game athletes ( Hausenblas and Symons Downs, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review is novel in its focus on the relationship of anthropometrics and/or body composition indicators with body image in athletes. Only two previous reviews have reported on associations of body measures and body image among athletes, both doing so as secondary objectives ( Hausenblas and Symons Downs, 2001 ; Zaccagni and Gualdi-Russo, 2023 ). In a 2001 review, Hausenblas and Symons Downs did not find differences in the magnitude of the effect size between individuals with BMI < 20 kg/m 2 , 20–22 kg/m 2 , and > 22 kg/m 2 ( Hausenblas and Symons Downs, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations